Nonlinear Analysis of Growth’s Effect on Debt: Finding the Threshold - Triwibowo, Sugeng; Oktaviani, Defy; Nurfika (Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: This paper explores the nonlinear effect of economic growth on the accumulation of public debt for groups of countries, based on their income levels, by finding its threshold estimator. Background Problems: The existing literature has discussed the debt's effect on growth intensively. Thus, empirical analysis to observe the inverse relationship between both variables is needed. Novelty: This paper confirms the negative and nonlinear impact of economic growth on public debt, and finds the threshold levels of economic growth on debt in high-income countries (HIC) and low-and middle-income countries (LMIC). Research Methods: We employed OLS panel regression with data covering 62 countries from 1970 to 2015. The fixed-effect panel threshold model is used to estimate the threshold level of economic growth that affects debt accumulation. Finding/Results: We found that economic growth reduces the public debt in the long run. In HIC, we find two threshold levels of economic growth, at 2.92% and at 8.41%. Moreover, in LMIC, a single threshold is found at 11.61%. Conclusion: It is proven that maintaining robust economic growth could reduce debt accumulation in the long run, the magnitude of the impacts varies between HIC and LMIC.